A patient feedback reporting tool for OpenNotes: implications for patient-clinician safety and quality partnerships. Issue 4 (13th December 2016) - Bell, Sigall K; Gerard, Macda; Fossa, Alan; Delbanco, Tom; Folcarelli, Patricia H; Sands, Kenneth E; Sarnoff Lee, Barbara; Walker, Jan
Abstract : Background: OpenNotes, a national movement inviting patients to read their clinicians' notes online, may enhance safety through patient-reported documentation errors. Objective: To test an OpenNotes patient reporting tool focused on safety concerns. Methods: We invited 6225 patients through a patient portal to provide note feedback in a quality improvement pilot between August 2014 and 2015. A link at the end of the note led to a 9-question survey. Patient Relations personnel vetted responses, shared safety concerns with providers and documented whether changes were made. Results: 2736/6225(44%) of patients read notes; among these, 1 in 12 patients used the tool, submitting 260 reports. Nearly all (96%) respondents reported understanding the note. Patients and care partners documented potential safety concerns in 23% of reports; 2% did not understand the care plan and 21% reported possible mistakes, including medications, existing health problems, something important missing from the note or current symptoms. Among these, 64% were definite or possible safety concerns on clinician review, and 57% of cases confirmed with patients resulted in a change to the record or care. The feedback tool exceeded the reporting rate of our ambulatory online clinician adverse event reporting system several-fold. After a year, 99% of patients and care partners found the tool valuable, 97% wanted it to continue, 98% reported unchanged or improved relationships with their clinician, and none of the providers in the small pilot reported worsening workflow or relationships with patients. Conclusions: Patients and care partners reported potential safety concerns in about one-quarter of reports, often resulting in a change to the record or care. Early data from an OpenNotes patient reporting tool may help engage patients as safety partners without apparent negative consequences for clinician workflow or patient-clinician relationships.